Praying 'Regularly' (not 'Constantly') A Note on the Cultic Background of dia pantos at Luke 24:53, Acts 10:2 and Hebrews 9:6, 13:15 - Hamm, M. Dennis 1936- (2004)
Discusses the special use of the idiom dia pantos or time reference in the Septuagint in cultic passages. Description of the risen Jesus Christ and his death based on Luke 24:53; Comparison between dia pantos and one's personal prayer with the Tamid service; Definition of the phrase dia pantos in the New Testament.
Keywords: Bibel; Bibel; Bibel; Apocryphal Acts of the Apostles; Apocryphal books (New Testament); Bible -- Criticism, interpretation, etc; Jesus Christ; Tamid; Theology